Prolonged adrenal suppression after osilodrostat discontinuation in a patient with Cushing’s disease with eventual hypercortisolism relapse: Case Report and literature review - Dzialach, Lukasz; Respondek, Wioleta; Siejka, Anna; Witek, Przemyslaw (Frontiers in Medicine, 2025)
Osilodrostat is a potent oral steroidogenesis inhibitor that is an effective medical therapy in the management of patients with endogenous Cushing syndrome. However, due to its high therapeutic potential, it is associated with a high risk of inducing adrenal insufficiency (AI). Recently, it has also been reported that patients may experience prolonged adrenal suppression during osilodrostat treatment that persists despite its withdrawal. In this paper, we present a male patient with persistent Cushing’s disease (CD) who experienced several episodes of AI during long-term treatment with osilodrostat. Ultimately, due to the patient’s very low dose of osilodrostat, it was decided to discontinue the therapy after 270 weeks in total. Following the cessation of osilodrostat, the patient commenced treatment with recombinant human growth hormone due to severe growth hormone deficiency, which revealed an underlying cortisol deficiency, likely caused by a prolonged adrenocortical blockage induced by osilodrostat, requiring the initiation of hydrocortisone replacement therapy. During and after the osilodrostat therapy, we additionally observed a low serum concentration of dehydroepiandrosterone sulfate (DHEA-S) despite elevated plasma adrenocorticotrophin. This finding suggested potential inhibition of adrenal steroidogenesis upstream of 11β-hydroxylase. A urine steroid profile performed 40 weeks after discontinuing osilodrostat showed reduced or borderline excretion of cortisol metabolites, as well as significantly decreased excretion of DHEA metabolites. Finally, 62 weeks after the last exposure to osilodrostat, the patient presented with clinical and biochemical features of relapse of hypercortisolemia, and osilodrostat was reintroduced. This case highlights the importance of close monitoring in patients treated with osilodrostat, as hypocortisolemia can arise suddenly and unexpectedly at any point during treatment, even in those on stable doses. Additionally, it indicates that osilodrostat has the potential to induce prolonged adrenal blockade, even after treatment has ceased. The unexpected persistence of adrenal suppression suggests unknown long-term effects of osilodrostat that require further investigation.